Application of Data Mining Algorithm to Investigate the Effect of Intelligent Transportation Systems on Road Accidents Reduction by Decision Tree - Khabiri, Mohammad Mehdi; Ghahfarokhi, Fatemeh Matin; Sarfaraz, Sara; Anaie, Hasan Mohammadi (Communications - Scientific letters of the University of Zilina, 2022)
Due to the large amount of available data in this study, authors have utilized data mining algorithms, especially the decision tree, to process these data and obtain the information, which would result in increasing road safety, determining the causes affecting it and patterns leading to traffic accidents. The effective use of this tool and its role in controlling the number of driving accidents is the subject of this study with the help of data mining algorithms. The results show that the increase in the number of roadside assistances to more than 41; number of driving accidents (fatally injured) is not significantly different, hence one of the proposed strategies for intelligent relay stations and its organization with the intelligent transportation tool is available. The intelligent transportation system utilities comprise of monitoring, guidance and enforcement tools, plus service tools such as rescue, driver assistant and road improvement.